Ferromagnetic resonance in nanomagnetic metal core and noble metal shell systems - Bala, Tanushree; Enoki, Toshiaki; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
The change in the line widths in the ferromagnetic resonance (FMR) spectra of Co and Ni nanoparticles upon shell formation with noble metals like gold or silver are described. The NicoreAgshell, CocoreAgshell, and CocoreAushell nanoparticles were prepared by a simple transmetallation reaction between the Co and Ni nanoparticles and the Ag+ or AuCl−4 ions. It is revealed that the FMR line width decreases upon Ag shell formation whereas it increases upon core–shell composite formation with Au. Several probable explanations such as the differences in size distributions before and after the reaction or the changes occurring in shape anisotropy of the particles due to the shell formation or the different extents of electronic interaction between the core and shell materials have been offered for this observation.
Keywords: Fmr Study; Line Width Comparison; Magnetic Core-Noble Metal Shell Nanoparticles